Difficulty Learning SKI for Students with Elementary School Background at MTs Negeri 2 Bengkulu City - Putri Julia; Inayah Latifah; Ismanur Hasanah; Anggun Tamara Tamesty; Jeni Efri Yani; Adicky Faturrahman; Hartoni Chandra (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This research aims to look at the conditions and situations in the learning process of Islamic Cultural History (SKI) at MTs Negeri 2 Bengkulu City. The research method used by researchers is a qualitative method which explains descriptively about SKI learning in this research using direct observation and interview methods by coming to the research location and directly to the r esearch subjects so that data collection can be carried out more effectively. Researchers found one problem at MTs Negeri 2 Bengkulu City, namely students' learning difficulties which affected students' interest, motivation and learning success. From this research, it was found that what causes learning difficulties for students at Mts Negeri 2 Bengkulu City is related to differences in students with elementary school and SD IT/MI educational backgrounds before entering MTs Negeri 2 Bengkulu City.